A systematic review of participation of young people in healthcare. (4th April 2011) - Morgan, J; Watts, R; Wall, J; Wood, D M
Abstract : Aim: To determine the most effective and cost-effective methods of involving children and young people in health services. Methods: A systematic search of worldwide published and grey literature was performed to identify relevant English language articles published between 1 January 1990 and 1 January 2010. Two independent researchers reviewed the studies for eligibility and then carried out a structured quality assessment in line with published quality criteria. Where there was disagreement, this was resolved in consultation with a third researcher. Key themes and the level of young people's participation were then identified from included studies. Results: Of 39 reports identified 20 were suitable for inclusion. The included studies and reports were all qualitative in nature (100%) and often described the views of young people on the quality of health services. Other studies described young people's involvement in developing health policy, health education and health research. The studies largely involved adolescents and young adults (10–19 years) with 4 (20%) including younger school age children (4–9 years). The studies were undertaken in a variety of settings including within hospital (7, 35%), mental health (4, 20%), sexual health (3, 15%), and in primary care or community health services (7, 35%). Overall the level of young people's participation described in the studies was relatively low, with 14 (70%) categorised as 'assigned but informed'. In 6 (30%) there was a higher level of young people's participation and in these studies young people's participation appeared to have a greater impact. COREQ assessments of study quality revealed a number of deficiencies in many of the reports. Conclusions: Involvement of children and young people in the development of healthcare services appears to be most effective when young people are involved early in the planning process and when they have greater influence in decision-making. There were a number of reports of the successful application of novel and creative methods for involving young people, but further research is needed to assess the impact and cost effectiveness of young people's participation in health services.